ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH ( PAD ) DI KABUPATEN KETAPANG PERIODE TAHUN 2000 2012 - B61110044, IRWAN DWIYONO (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACTRegional autonomy has been carried out giving a greater role to the Government and localeconomic actors in managing development in the area. Through decentralization, localgovernments have the authority to explore the role of the allocation of income and performindependently in setting development priorities .Revenue ( PAD ) is an important benchmark for determining the level of local capacity inimplementing real autonomy and responsibility .This study aims to determine how much influence the government expenditure and GDPaffect local revenues in Ketapang . The independent variables consist of : GovernmentSpending and GDP while the dependent variable is the original income . The analyticalmethod used was linear regression analysis . Government Spending result is not significantpositive effect on local revenues , and GDP is significantly positively affect local revenue (PAD ) . Whereas with GDP , government spending is significantly positive effect on revenue( PAD )Keywords: Government Spending, GDP and Revenue ( PAD )